Buckling of Nonprismatic Column on Varying Elastic Foundation with Arbitrary Boundary Conditions - Ghadban, Ahmad A.; Al-Rahmani, Ahmed H.; Rasheed, Hayder A.; Albahttiti, Mohammed T. (My University, 2017)
Buckling of nonprismatic single columns with arbitrary boundary conditions resting on a nonuniform elastic foundation may be considered as the most generalized treatment of the subject. The buckling differential equation for such columns is extremely difficult to solve analytically. Thus, the authors propose a numerical approach by discretizing the column into a finite number of segments. Each segment has constants  (modulus of elasticity),  (moment of inertia), and  (subgrade stiffness). Next, an exact analytical solution is derived for each prismatic segment resting on uniform elastic foundation. These segments are then assembled in a matrix from which the critical buckling load is obtained. The derived formulation accounts for different end boundary conditions. Validation is performed by benchmarking the present results against analytical solutions found in the literature, showing excellent agreement. After validation, more examples are solved to illustrate the power and flexibility of the proposed method. Overall, the proposed method provides reasonable results, and the examples solved demonstrate the versatility of the developed approach and some of its many possible applications.
Citation: Ahmad A. Ghadban, Ahmed H. Al-Rahmani, Hayder A. Rasheed, and Mohammed T. Albahttiti, “Buckling of Nonprismatic Column on Varying Elastic Foundation with Arbitrary Boundary Conditions,” Mathematical Problems in Engineering, vol. 2017, Article ID 5976098, 14 pages, 2017. doi:10.1155/2017/5976098